2022
DOI: 10.3390/v14030568
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence, Waning and Correlates of Anti-SARS-CoV-2 IgG Antibodies in Tyrol, Austria: Large-Scale Study of 35,193 Blood Donors Conducted between June 2020 and September 2021

Abstract: There is uncertainty about the seroprevalence of anti-SARS-CoV-2 antibodies in the general population of Austria and about the waning of antibodies over time. We conducted a seroepidemiological study between June 2020 and September 2021, enrolling blood donors aged 18–70 years across Tyrol, Austria (participation rate: 84.0%). We analyzed serum samples for antibodies against the spike or the nucleocapsid proteins of SARS-CoV-2. We performed a total of 47,363 samples taken from 35,193 individuals (median age, 4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 26 publications
(33 reference statements)
7
28
2
Order By: Relevance
“…It is striking that the seroprevalence among unvaccinated participants with one or more COVID-19 positive tests was only 68.7%. This observation is different than the one identified in a Austrian seroprevalence study among unvaccinated blood donors [ 10 ] and in a US study evaluating the prevalence of antibodies among unvaccinated US adults [ 24 ]. The lower seroprevalence identified in this study could be explained by the fact that the time since the infection was not considered in our analyses.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…It is striking that the seroprevalence among unvaccinated participants with one or more COVID-19 positive tests was only 68.7%. This observation is different than the one identified in a Austrian seroprevalence study among unvaccinated blood donors [ 10 ] and in a US study evaluating the prevalence of antibodies among unvaccinated US adults [ 24 ]. The lower seroprevalence identified in this study could be explained by the fact that the time since the infection was not considered in our analyses.…”
Section: Discussioncontrasting
confidence: 93%
“…SalivaHIS results were compared with other national and international seroprevalence studies that were conducted during the same study period. From these studies it appears that the seroprevalence was 66.1% in the general population in Geneva (July 2021) [ 8 ], 89.4% in the general population in England (July 2021) [ 11 ], 75.9% among blood donors in Austria (July 2021) [ 10 ], and 98.0% (July 2021) among Belgian blood donors [ 12 ]. The seroprevalence of 78.1% (July 2021) observed in our study is, thus, relatively consistent with what was found in those other studies [ 8 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations